2012
DOI: 10.1111/j.1750-3841.2012.02736.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds in Lipid Fractions of Pumpkin (Cucurbita sp) Seeds for Use in Food

Abstract: Bioactive compounds, besides presenting basic nutritional functions, provide metabolic and physiological health benefits when consumed as part of the usual diet. Therefore, there is a growing interest in vegetable oils of special composition, such as the ones extracted from fruit seeds. The seeds of Cucurbita sp are shown to be promising sources of oils, and especially the Cucurbita moschata and maxima species have not yet been fully elucidated. For this reason, it becomes important to investigate the chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 27 publications
2
22
0
1
Order By: Relevance
“…Plants belonging to the Cucurbitaceae family may possess pharmacological properties (Talukdar & Hossain, 2014;Vijayakumar, Eswaran, Ojha, Rao Ch & Rawat, 2011), including antidiabetic role (Chandrasekar, Mukherjee & Mukherjee, 1989;Huseini, Darvishzadeh, Heshmat, Jafariazar, Raza & Larijani, 2009;Rashidi, Mirhashemi, Taghizadeh & Sarkhail, 2013 ), anti-ulcer role, analgesic, nephro-protection (Jain & Singhai, 2010 ), and anticancer effects (Vijayakumar et al, 2011 ).Pumpkin (Cucurbita pepo L) was extensively investigated for uses in herbal therapy (Abdel-Rahman, 2006) and as a source of bioactive food compounds (Veronezi & Jorge, 2012). Less wellinvestigated cucurbitaceae are now receiving attention related to both food and medicinal applications (Milind & Kulwant, 2011;Talukdar & Hossain, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Plants belonging to the Cucurbitaceae family may possess pharmacological properties (Talukdar & Hossain, 2014;Vijayakumar, Eswaran, Ojha, Rao Ch & Rawat, 2011), including antidiabetic role (Chandrasekar, Mukherjee & Mukherjee, 1989;Huseini, Darvishzadeh, Heshmat, Jafariazar, Raza & Larijani, 2009;Rashidi, Mirhashemi, Taghizadeh & Sarkhail, 2013 ), anti-ulcer role, analgesic, nephro-protection (Jain & Singhai, 2010 ), and anticancer effects (Vijayakumar et al, 2011 ).Pumpkin (Cucurbita pepo L) was extensively investigated for uses in herbal therapy (Abdel-Rahman, 2006) and as a source of bioactive food compounds (Veronezi & Jorge, 2012). Less wellinvestigated cucurbitaceae are now receiving attention related to both food and medicinal applications (Milind & Kulwant, 2011;Talukdar & Hossain, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that γ-tocopherol is the isomer that stood out in the lipid fractions and in the seeds, mainly in Menina Brasileira (Veronezi and Jorge, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Several species of great economic interest are included in this group, with the most popular being cucumber (Cucumis sativus L.), watermelon (Citrullus vulgaris S.), melon (Cucumis melo L.) and summer and winter pumpkin (Cucurbita spp.). Among the pumpkin species belonging to the genus Cucurbita, the most cultivated in the world are Cucurbita pepo L., C. moschata L. and C. maxima L. (GONZAGA et al, 1999;LOY, 2004;PARIS and BROWN, 2005;VERONEZI and JORGE, 2012).…”
Section: Introductionmentioning
confidence: 99%